Comparative pharmacokinetics and safety evaluation of high dosage regimens of Andrographis paniculata aqueous extract after single and multiple oral administration in healthy participants - Songvut, Phanit; Rangkadilok, Nuchanart; Pholphana, Nanthanit; Suriyo, Tawit; Panomvana, Duangchit; Puranajoti, Porranee; Akanimanee, Jaratluck; Satayavivad, Jutamaad (Frontiers in Pharmacology, 2023)
Background: The prolonged situation of the COVID-19 pandemic, with the emergence of new variants of SARS-CoV-2, not only imposes a financial burden on healthcare supports but also contributes to the issue of medication shortages, particularly in countries with limited access to medical resources or developing countries. To provide an alternative therapeutic approach during this crisis, there is an increasing research that has investigated the potential uses of Andrographis paniculata in supporting the application of herbal medicine for COVID-19. Purpose: This study aimed to investigate the safety profiles and clinical pharmacokinetics, specifically focusing on dose proportionality of the four major active diterpenoids of Andrographis paniculata aqueous extract following oral administration of two different high doses of andrographolide. Methods: The participants received the aqueous extract capsules equivalent to 60 or 120 mg of andrographolide; and as multiple doses administered three times daily, calculated as 180 or 360 mg/day of andrographolide. Safety evaluation was assessed following the oral administration of the multiple doses. Results: The results indicated a dose-dependent effect observed between the respective two doses. A twofold increase in the dose of the extract demonstrated twofold higher plasma concentrations of the four major parent compounds; 1) andrographolide, 2) 14-deoxy-11, 12-didehydroandrographolide, 3) neoandrographolide, and 4) 14-deoxyandrographolide, as well as their conjugated metabolites. The observed diterpenoids are biotransformed partly through a phase II metabolic pathway of conjugation, thus reducing in the parent compounds in the plasma and existing the majority as conjugated metabolites. These metabolites are then excreted through the hepatobiliary system and urinary elimination. For the results of the safety evaluation, the occasional adverse events experienced by individuals were of mild intensity, infrequent in occurrence, and reversible to the normal baseline. Safety consideration should be given to the individual patient’s pertinent health conditions when using this extract in patients with hepatic or kidney dysfunction. Clinical Trial Registration:https://www.thaiclinicaltrials.org/show/TCTR20210201005; Identifier: TCTR20210201005.